The electromagnetic field potentials of an arbitrary charge and current distribution in Coulomb gauge - Furs, Alexander N. (Journal of the Belarusian State University. Physics, 2017)
The field potentials of an arbitrary charge and current distribution are calculated in Coulomb gauge. It is shown that the vector potential is determined by not only the current density values at the retarded time but also prehistory of the charge density variation over the interval from the retarded time to the current time. Various representations of the Liénard – Wiechert potentials are obtained in Coulomb gauge. They are applied to the case of a uniform rectilinear moving point charge.
Keywords: gauge invariance; Lorenz and Coulomb gauge; retarded potentials; Liénard – Wiechert potentials